Free Will and Weak Will in Donald Davidson - Maciaszek, Janusz (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
In the paper I present Donald Davidson’s solution of the problem of freedom against the background of his complex philosophical system. In spite of the fact that freedom understood as anomality was justified by Davidson by means of his philosophy of language I argue that it can be fully appreciated against the background of his philosophy of action. I argue also that the phenomenon of weak will explained by Davidson in terms of prima facie judgements and sans-phrase judgement is a necessary condition of freedom conceived as anomaly. In the end I indicate that in spite of superficial analogies suggested by Davidson his solution of the problem of freedom is incomparable with the Kantian one.